Disrupting the spatio-temporal symmetry of the electron dynamics in atmospheric pressure plasmas by voltage waveform tailoring. (7th January 2019) - Gibson, Andrew R; Donkó, Zoltán; Alelyani, Layla; Bischoff, Lena; Hübner, Gerrit; Bredin, Jérôme; Doyle, Scott; Korolov, Ihor; Niemi, Kari; Mussenbrock, Thomas; Hartmann, Peter; Dedrick, James P; et al.
Abstract: Single frequency, geometrically symmetric Radio-Frequency (RF) driven atmospheric pressure plasmas exhibit temporally and spatially symmetric patterns of electron heating, and consequently, charged particle densities and fluxes. Using a combination of phase-resolved optical emission spectroscopy and kinetic plasma simulations, we demonstrate that tailored voltage waveforms consisting of multiple RF harmonics induce targeted disruption of these symmetries. This confines the electron heating to small regions of time and space and enables the electron energy distribution function to be tailored.